Legal Reasoning of the Deconstruction of Protection Patters Ambiguity to Home-Based Workers in Indonesia’s Labor Law - Imron, Ali (Richtmann Publishing, 2019)
Increasingly widespread of self-employment and bulk jobs are triggered by the pressures of labor market flexibility, production process externality, and the high level of unemployment. One reason for this situation is the effects of globalization which stimulates transnational production system through the expansion of global supply chain in developing countries. Indonesia attempts to stay afloat of the competition by inviting transnational corporations to operate within it, offering low wage incentives and natural resources abundant to attract them. The purpose of this study is to examine the legislative products and policies of employment which are ambiguous in guaranteeing work protection for home-based workers, particularly the essential factors that hinder home-based workers from obtaining the assurance of the minimum standards of decent work in industrial employment relationships. The methodology that is used is based on empirical data followed by an evaluative examination on the interrelation between norms and facts. It is focused on deductive and inductive logic that reconstructs the construct of legal system in the field of labor, evaluates intensively the compliance with current provisions, and recommends currently required substantial changes in regulations and policies. A post-modern thought has emerged as a form of resistance to the state’s hegemonic power of the law which demands that the dominant influences be gradually limited. Accordingly, a progressive law paradigm has been formed to delineate a legal reasoning to loosen the shackles of legal positivism. Legal transformation creates a bifurcation of legal patterns which are formalist, rationalist, and procedural-based, but in addition there is also the idea of giving precedence to substantial justice. It is also found that a legal enforcement which is bound to the literal implementation of law has a strong tendency to interpret the rule of law rigidly. It is important to adopt a progressive legal approach which promotes the fulfilment of the sense of substantial justice.